Risco sistêmico e regulação bancária no Brasil - Datz, Marcelo Davi Xavier da Silveira (2002)
This research analyses the measures adopted in Brazil to reduce the risk of systemic financial crises. A comparison between these measures and the suggestions of the Multilateral Organisms is made, looking for evaluating the degree of adherence to the international standards of reference. Some models presented intend to explain the occurrence of systemic crises in the financial system and examine the reasons that turn it into a more vulnerable sector for the occurrence of these events.